Effects of Different Natural Additives Alternative to Chemical Ones on Artisanal Bologna-Type Sausages Shelf Life - Marica Egidio; Marika Di Paolo; Loriana Casalino; Valeria Vuoso; Sophia Alesio; Alma Sardo; Raffaele Marrone (Applied Sciences)
This study aims to evaluate the effects of mandarin peel (Citrus reticulata L.), oregano (Origanum vulgare), and common lambsquarter (Chenopodium album) powders as natural additives on the shelf lives of artisanal Bologna-type sausages by comparing them with a chemically preserved control formulation. In this regard, four mortadella formulations (MTS1, MTS2, MTS3, and MTC) were produced and analyzed for physicochemical, microbiological, rheological, and sensory properties at days 1 (T0), 15 (T1), 25 (T2), and 30 (T3) after vacuum packaging. The results highlighted greater performances in the experimental samples MTS2 (made with common lambsquarters) and MTS3 (made with oregano), particularly in microbiological stability and antioxidant activity, which were similar to those of the control sample (MTC), with TBAR values extremely low, even at the end of the storage for both MTS2 (0.65 mg MDA/kg) and MTS3 (1.11 mg MDA/kg), reflecting effective lipid oxidation control. The sensory analysis further revealed oregano-containing mortadella (MTS3) as the most preferred sample for appearance and taste. These findings suggest that natural additives, like oregano or lambsquarter powders, could replace or complement nitrites in Bologna-type sausages, ensuring product quality, safety, and shelf life while meeting consumer demand for clean-label and chemical-additive-free products. Further research could optimize these formulations to support commercial applications.